Rapid host switching in generalist Campylobacter strains erodes the signal for tracing human infections - Ben Pascoe (The ISME Journal, 2015)
Campylobacter jejuni and Campylobacter coli are the biggest causes of bacterial gastroenteritis in the developed world, with human infections typically arising from zoonotic transmission associated with infected meat, especially poultry. Because this organism is not thought to survive well outside of the gut, host associated populations are genetically isolated to varying degrees. Therefore the likely origin of most Campylobacter strains can be determined by host associated variations in the genome. This is instructive for characterizing the source of human infection, at the population level, using seven-locus multilocus sequence typing. However, some common strains, notably isolates belonging to the ST-21, ST-45 and ST-828 clonal complexes, appear to have broad host ranges, hindering source attribution. Whole genome sequencing has the potential to reveal fine-scale genetic structure associated with host specificity within each of these strains. Here we report that, surprisingly, rates of zoonotic transmission among animal species within these strains are so high that whole genomes confer limited power to pinpoint the host animal reservoir. Our results are consistent with adaptation of these strains to a generalist lifestyle, allowing them to exploit opportunities for rapid transmission between mammal and bird hosts. Further, they indicate that pinpointing the source of individual human infections via genomics will require intensive sampling of animal reservoir populations.